New technology in schools: is there a payoff? - Stephen Machin; Sandra McNally; Olmo Silva (Institute for the Study of Labor (IZA), 2006)
Despite its high relevance to current policy debates, estimating the causal effect of Information Communication Technology (ICT) investment on educational standards remains fraught with difficulties. In this paper, we exploit a change in the rules governing ICT funding across different school districts of England to devise an instrumental variable strategy to identify the causal impact of ICT expenditure on pupil outcomes. The approach identifies the effect of being a 'winner' or a 'loser' in the new system of ICT funding allocation to schools. Our findings suggest a positive impact on primary school performance in English and Science, though not for Mathematics. We reconcile our positive results with others in the literature by arguing that it is the joint effect of large increases in ICT funding coupled with a fertile background for making an efficient use of it that led to positive effects of ICT expenditure on educational performance in English primary schools.
Keywords: H52; I20; I28; J24; 330; Information and Communication Technology (ICT); pupil achievement; Allgemeinbildende Schule; Computergestütztes Verfahren; Bildungsforschung; Großbritannien; Allgemeinbildende Schule; Computergestütztes Verfahren; Bildungsforschung; Großbritannien